2015
DOI: 10.1155/2015/413276
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Patients with Type 2 Diabetes Mellitus in Dubai: A HEDIS-Like Assessment

Abstract: Objective. As little data are available on the quality of type 2 diabetes mellitus (T2DM) care in the Arabian Gulf States, we estimated the proportion of patients receiving recommended monitoring at the Dubai Hospital for T2DM over one year. Methods. Charts from 150 adults with T2DM were systematically sampled and quality of care was assessed during one calendar year, using a Healthcare Effectiveness Data and Information Set- (HEDIS-) like assessment. Screening for glycosylated haemoglobin (HbA1c), low-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…The current study adds to the limited pool of studies on the same topic in the region. In conformity with Szabo's study in the UAE that found all UAE clinical care indicators exceed the US HEDIS diabetes care measure except for the HbA1c [6]; our study results also showed most clinical indicators exceed Szabo's study results [6] and the BRFSS benchmarks except for the HbA1c.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The current study adds to the limited pool of studies on the same topic in the region. In conformity with Szabo's study in the UAE that found all UAE clinical care indicators exceed the US HEDIS diabetes care measure except for the HbA1c [6]; our study results also showed most clinical indicators exceed Szabo's study results [6] and the BRFSS benchmarks except for the HbA1c.…”
Section: Discussionsupporting
confidence: 90%
“…In keeping with findings in similar studies [6, 18], metformin was the most prescribed diabetes medication at 89.9%. The second most prescribed medication comprised DDP-4 inhibitors (61.1%), and the third most prescribed medication comprised sulfonylureas (49.3).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations